Effect of material position on microstructure and mechanical properties of friction stir welded dissimilar austenite–ferrite stainless steels joints. Issue 12 (18th June 2021) - Guo, Guolin; Shen, Yifu; Wu, Kehan; Yan, Yuxiang
Abstract: The friction stir welding of 304 austenitic stainless steel and 430 ferritic stainless steel was performed by placing 304 plate on advancing side and retreating side of the tool, respectively. The results indicated that when the 304 plate was placed on advancing side, the weld metal showed superior flow characteristics and better material mixing compared to the weld when the 304 plate was placed on retreating side. The stir zone showed different characteristics including banded structure, subgrains and fine composite structure of austenite and ferrite because of dynamic recrystallization. The strain rate in austenitic stainless steel had a major effect on grain refinement and plastic deformation. The mechanical properties tests indicated that grain refinement combined with substructure and boundary martensite increased hardness and tensile strength when placing 304 plate on advancing side. The voids in stir zone resulted in a significant decrease in strength and elongation when placing 304 plate on retreating side. Overall, placing austenitic stainless steel on advancing side is more suitable for friction stir welded dissimilar austenite–ferrite stainless steels.